Exploring How Teacher Competency Development Influences Affective Work Outcomes - Adang Hambali; Asep Abdullah; Sally Badriyati (CV. Tripe Konsultan, 2026)
Understanding the role of professional development in shaping teachers’ workplace attitudes is essential for improving school performance and organizational effectiveness. In this context, the present study used a quantitative ex post facto approach to investigate how teacher competency development affects teacher loyalty, work discipline, and work motivation in 14 MTsN schools across Tasikmalaya Regency. The analysis shows that competency development has a positive and statistically significant impact on teacher loyalty and work motivation, indicating that improvements in pedagogical, professional, social, and personal competencies are linked to stronger institutional commitment and higher enthusiasm in performing teaching duties. The findings also reveal a significant relationship between competency development and work discipline, although the strength of this effect is comparatively weaker than its influence on loyalty and motivation. This relatively smaller effect may be explained by the complex nature of work discipline, which is shaped not only by competency enhancement but also by broader organizational factors such as school culture, leadership practices, and institutional rules and policies.